1997
DOI: 10.5962/bhl.title.112258
|View full text |Cite
|
Sign up to set email alerts
|

Rangeland reference areas : Castle River range condition and trend from 1953-1995 /

Abstract: The Rangeland Reference Area program administered by the Land and Forest Service was established by the Eastern Rockies Forest Conservation Board to assess range condition and monitor trend on rangelands within the boundaries of the Rocky Mountain Forest Reserve (RMFR). Forty-five fenced exclosures have been established in the Forest Reserve. These exclosures include permanently marked grazed and ungrazed transects. Species composition data has been recorded on these transects since 1953 when many of the sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Differences in moisture adaptation could explain the ability of undisturbed late‐seral stands of F. campestris to limit P. pratensis invasion in long‐term grazing exclosures across the region, particularly with intermittent drought (e.g. see Willoughby ). The corresponding competitive outcome between juveniles of these two grass species, however, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in moisture adaptation could explain the ability of undisturbed late‐seral stands of F. campestris to limit P. pratensis invasion in long‐term grazing exclosures across the region, particularly with intermittent drought (e.g. see Willoughby ). The corresponding competitive outcome between juveniles of these two grass species, however, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear how the invasion of Kentucky bluegrass onto the site will affect the succession towards a rough fescue dominated community type. Observations from other rangeland reference areas have shown that rough fescue will succeed back into a Kentucky bluegrass dominated community type in 25-30 years (Willoughby 1995), but it took 36 years before rough fescue again dominated this site on the ungrazed inside transect.…”
Section: Range Conditionmentioning
confidence: 98%
“…However, if the present grazing pressure continues Kentucky bluegrass will likely dominate the site. Recovery of this grassland back to a rough fescue dominated community type will likely take 20-30 years (Willoughby 1996). This community type was described on mesic, lower slope positions with shallow, nutrient poor soils.…”
Section: Plant Composition Canopy Cover(%)mentioning
confidence: 99%
“…Protection or a reduction in stocking level at the point where Kentucky bluegrass has become a significant component of the community allows rough fescue to recover, but it seems Kentucky bluegrass also remains as codominant. Willoughby (1996), found that some rangeland reference area sites which were protected from grazing before Kentucky bluegrass became established recovered to Rough fescue-Idaho fescue-Parry oatgrass in 20-30 years. In contrast sites that had significant Kentucky bluegrass invasion recovered to Rough fescue-Kentucky bluegrass dominated sites over the same time period.…”
Section: Plant Composition Canopy Coversmentioning
confidence: 99%